Impact of fetal growth restriction on neurodevelopmental outcome at 2 years for extremely preterm infants: a single institution study. (13th August 2016) - El Ayoubi, Mayass; Patkai, Juliana; Bordarier, Cécile; Desfrere, Luc; Moriette, Guy; Jarreau, Pierre‐Henri; Zeitlin, Jennifer
Abstract : Aim: We evaluated the impact of fetal growth restriction on neurodevelopmental outcomes at 2 years corrected age for infants born before 27 weeks gestational age. Method: Data on infants born before 27 weeks gestational age between 1999 and 2008 ( n =463), admitted to a tertiary neonatal unit in Paris, were used to compare neurological outcomes at 2 years for infants with birthweight lower than the 10th centile and birthweight of at least the 10th centile, using intrauterine reference curves. Outcomes were cerebral palsy (CP) and the Brunet‐Lézine assessment of cognitive development, which provides age‐corrected overall and domain‐specific (global and fine motor skills, language and social interaction) developmental quotients. Models were adjusted for perinatal and social factors. Results: Seventy‐two percent of infants were discharged alive. Eighty‐three percent ( n =268) were evaluated at 2 years. Six percent had CP. Fetal growth restriction was not associated with the risk of CP. After adjustment, children with a birthweight lower than the 10th centile had a global developmental quotient 4.7 points lower than those with birthweight of at least the 10th centile ( p <0.001); differences were greatest for fine motor and social skills (−4.7, p =0.053 and −7.3, p <0.001 respectively). Interpretation: In extremely preterm children, fetal growth restriction was associated with poorer neurodevelopmental outcomes at 2 years, but not with CP. What this paper adds: Overall developmental quotients were lower for extremely preterm infants with fetal growth restriction. Fine motor and social interaction skills were most affected. Cerebral palsy was not associated with fetal growth restriction.